2014
DOI: 10.1080/19440049.2014.975752
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of multiple mycotoxins and cyanogenic glucosides in cassava samples from Tanzania and Rwanda by an LC-MS/MS-based multi-toxin method

Abstract: A multi-mycotoxin method based on liquid chromatography/tandem mass spectrometry (LC-MS/MS) was used for a mycotoxin survey in 627 samples of processed cassava collected from different districts across Tanzania and Rwanda after the method performance for this matrix had been determined. Matrix effects as well as extraction efficiencies were found to be similar to most other previously investigated matrices with the exception of distinct matrix effects in the negative ionisation mode for early eluting compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 32 publications
1
38
4
Order By: Relevance
“…This florescence phenomenon is widely accepted for aflatoxins. Thin layer chromatography (TLC) is among one of the oldest techniques used for aflatoxin detection (Fallah et al, 2011), while high performance liquid chromatography (HPLC), liquid chromatography mass spectroscopy (LCMS), and enzyme linked immune-sorbent assay (ELISA) are the methods most frequently used for its detection (Tabari et al, 2011; Andrade et al, 2013; Sulyok et al, 2015). ELISA can be used to identify aflatoxins based on estimation of AfB1-lysine (metabolite of AFB1 toxin) concentration in the blood.…”
Section: Detection Techniquesmentioning
confidence: 99%
“…This florescence phenomenon is widely accepted for aflatoxins. Thin layer chromatography (TLC) is among one of the oldest techniques used for aflatoxin detection (Fallah et al, 2011), while high performance liquid chromatography (HPLC), liquid chromatography mass spectroscopy (LCMS), and enzyme linked immune-sorbent assay (ELISA) are the methods most frequently used for its detection (Tabari et al, 2011; Andrade et al, 2013; Sulyok et al, 2015). ELISA can be used to identify aflatoxins based on estimation of AfB1-lysine (metabolite of AFB1 toxin) concentration in the blood.…”
Section: Detection Techniquesmentioning
confidence: 99%
“…Since many plant biotransformation products of mycotoxins are not included in conventional analytical methods, also because no regulated limits exist for them in food commodities, they are called masked mycotoxins [18,19]. LC-MS/MS techniques based on multiple reaction monitoring mode are frequently used for the analysis of various (masked) mycotoxins in food products and raw materials [20,21,22]. However, much more accurate mass-to-charge ( m/z ) values are obtained by high-resolution MS (HRMS) including Orbitrap or quadrupole time-of-flight (Q-TOF) instruments.…”
Section: Introductionmentioning
confidence: 99%
“…All the samples met the proposed East Africa regulatory threshold of 10 Όg/kg. Similar observations regarding the low contamination by aflatoxins in cassava are reported in Ghana (Wareing, Westby, Gibbs, Allotey, & Halm, 2001), Republic of Benin (Adjovi et al., 2014; Gnonlonfin et al., 2012) and Tanzania (Sulyok et al., 2015) The occurrence of aflatoxins in cassava chips from Cameroon was only detected after 4 weeks’ storage (Essono et al., 2009). These results suggested that fresh cassava is safe regarding aflatoxin contamination; however, processing methods such as heat treatment, sun drying, or freezing may alter the ability of cassava to block toxinogenesis, leading to secondary contamination.…”
Section: Resultsmentioning
confidence: 99%